Deteksi Kematangan Buah Pisang Berdasarakan Kulit Menggunakan Metode Multi-Level Thresholding dan YCbCr - T. Rahmad Effendi; ade hermawan (E-Jurnal Universitas Samudra, 2021)
Banana (Musa Paradisiaca) is a fruit plant that is rich source of vitamins, minerals and carbohydrates [1]. At this time determining the ripeness of bananas is a problem in itself for banana farmers. To determine the ripeness of bananas, it is necessary to pay attention to the level of fruit maturity which is an important factor in the quality of the banana fruit. Banana fruit has 3 colors, namely green when the banana is raw, yellow when the banana is half ripe and the yellow-black color of the banana is very ripe. This research will use methods namely YCbCr and Multi-Level Thresholding, where the results are quite good.